DETERMINAN FINANCIAL DISTRESS PADA PT ANEKA TAMBANG, Tbk - Safika Zebua; Budi Gautama Siregar; Sarmiana Batubara; Aswadi Lubis (Jurnal Mahasiswa Akuntansi Samudra, 2024)
This study aims to analyze and provide an overview of financial performance proxied by Return On Assets, corporate governance mechanisms proxied by the audit committee and ownership structure proxied by managerial ownership in influencing the possibility of financial distress at PT Aneka Tambang, Tbk for the observation period 2015-2022. Financial distress in this study is measured using the Altman Z-Score method. The research population is the company's secondary data consisting of financial performance, corporate governance, ownership structure and financial distress from 2015-2022 which are taken quarterly, totaling 32 quarters. Sample withdrawal is used with purposive sampling technique with the criteria of published and accessible financial reports so that the number of samples obtained is 31 quarterly reports. This study found that financial performance proxied by Return on Assets can have a significant effect on the possibility of financial distress at PT Aneka Tambang, Tbk for the 2015-2022 observation period, corporate governance mechanisms proxied by the audit committee have no effect on financial distress, and ownership structure proxied by managerial ownership has no effect on the financial distress condition of PT Aneka Tambang, Tbk for the 2015-2022 observation period. Future reseachers can add observation periods to several companies such as using panel data and adding independent variables such as individual ownership and institutional ownership